ANALISI ISI OPINI PUBLIK TERKAIT CITRA DIRI GANJAR PRANOWO DI TWITTER - Bella Indah Permatasari (2023)
This study aims to find out how Indonesian public opinion relates to self-image carried out by Ganjar Pranowo on Twitter, using public opinion theory. The method used is quantitative content analysis method using primary and secondary data sources. The data collection technique is by using the document technique, namely by collecting tweet replies from Ganjar Pranowo's tweet threads in the period November 24 2022 - November 30 2022. Researchers use data analysis techniques with coding sheets and in filling out the coding sheets will be assisted by coders to compare and measure the accuracy of the researcher's assessment of the categories in the predetermined unit of analysis. The final results of this study show that public opinion regarding Ganjar Pranowo's self-image on Twitter from 24 - 30 November 2022 has a majority of negative sentiments. The Twitter public sees Ganjar Pranowo as unfit to be a leader, everything he does is just imaging. Form the best possible impression in the eyes of the Indonesian people so they can win the presidential election. However, there are also not a few opinions of Twitter netizens who have positive sentiments regarding the self-image of the man born in Karanganyar on October 28, 1968. Where, netizens believe in Ganjar Pranowo as a public official who has qualified performance and can lead Indonesia in the upcoming 2024-2029 period. As for netizens who have neutral sentiments, they are more focused on conveying their complaints to the Governor of Central Java.